Relocation of a Ca2+-dependent protein kinase activity during pollen tube reorientation - Moutinho, A (1998)
Pollen tube reorientation is a dynamic cellular event that is crucial for successful fertilization. We have shown previously that pollen tube orientation is regulated by cytosolic free calcium ([Ca2+]c). In this paper, we studied the activity of a Ca2+-dependent protein kinase during reorientation. The kinase activity was assayed in living cells by using confocal ratio imaging of BODIPY FL bisindolylmaleimide. We found that growing pollen tubes exhibited higher protein kinase activity in the apical region, whereas nongrowing cells showed uniform distribution. Modification of growth direction by diffusion of inhibitors/activators from a micropipette showed the spatial redistribution of kinase activity to predict the new growth orientation. Localized increases in [Ca2+]c induced by photolysis of caged Ca2+ that led to reorientation also increased kinase activity. Molecular and immunological assays suggest that this kinase may show some functional homology with protein kinase C. We suggest that the tip-localized gradient of kinase activity promotes Ca2+-mediated exocytosis and may act to regulate Ca2+ channel activity.